Detection of CO emission lines in the dayside atmospheres of WASP-33b and WASP-189b with GIANO - Yan, Fei; Pallé, E.; Reiners, A.; Casasayas-Barris, N.; Cont, D.; Stangret, M.; Nortmann, L.; Mollière, Paul Maurice; Henning, Thomas; Chen, G.; Molaverdikhani, Karan (Astronomy and astrophysics, 2022)
Ultra-hot Jupiters (UHJs) are expected to possess temperature inversion layers in their dayside atmospheres. Recent thermal emission observations have discovered several atomic and molecular species along with temperature inversions in UHJs. We observed the thermal emission spectra of two UHJs (WASP-33b and WASP-189b) with the GIANO-B high-resolution near-infrared spectrograph. Using the cross-correlation technique, we detected carbon monoxide (CO) in the dayside atmospheres of both planets. The detected CO lines are in emission, which agrees with previous discoveries of iron emission lines and temperature inversions in the two planets. This is the first detection of CO lines in emission with high-resolution spectroscopy. Further retrieval work combining the CO lines with other spectral features will enable a comprehensive understanding of the atmospheric properties such as temperature structures and C/O ratios. The detected CO and iron emission lines of WASP-189b have redshifted radial velocities of several km s−1, which likely originate from a dayside to nightside wind in its atmosphere. Such a redshifted velocity has not been detected for the emission lines of WASP-33b, suggesting that the atmospheric circulation patterns of the two UHJs may be different.
Gesehen am 10.08.2022